To rearrange the formula \( y = mx + b \) to solve for \( x \), the first step would be to isolate the term \( mx \). You can do this by subtracting \( b \) from both sides of the equation using the Property of Equality.
Here’s how it looks:
-
Start with the equation: \[ y = mx + b \]
-
Subtract \( b \) from both sides: \[ y - b = mx \]
Now, you have \( mx \) isolated on one side. The next steps would involve dividing by \( m \) to solve for \( x \):
- Divide both sides by \( m \): \[ x = \frac{y - b}{m} \]
This gives you \( x \) as the quantity of interest.